2014
DOI: 10.1111/hex.12231
|View full text |Cite
|
Sign up to set email alerts
|

Patient asthma networks: understanding who is important and why

Abstract: Background Multidisciplinary care (MDC) has been proposed as an essential component to the delivery of effective and efficient health care. However, patients have shown to establish their own sources of health advice and support outside the professional domain. It remained unclear as to how patients' choices may impact on MDC.Objective This study aimed to explore the role of patients in MDC, specifically (i) how and why patients select sources of health services, information and support, that is, their health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 36 publications
1
34
1
Order By: Relevance
“…Patients with LTCs encounter and interact with a wide range of healthcare and non-healthcare networks that shape how they engage in self-care [60]. Patients in this study suggested that while healthcare professionals provided self-care information and advice relating to their LTCs, use of prescribed medicines and lifestyle management, these were often provided didactically and passively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LTCs encounter and interact with a wide range of healthcare and non-healthcare networks that shape how they engage in self-care [60]. Patients in this study suggested that while healthcare professionals provided self-care information and advice relating to their LTCs, use of prescribed medicines and lifestyle management, these were often provided didactically and passively.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers pose significant direct and indirect economic costs and psychosocial burden [13], particularly evident in asthmatics with inadequate health literacy [14]. Instrumental and emotional support provided by robust social networks and informal caregivers is likely to overcome such barriers [1516] by assisting asthmatics in obtaining, processing, understanding and applying basic health information and services needed to make appropriate health decisions and meet daily self-management demands [171819]. Improvements in asthma integrated care might thus be achieved through in-depth knowledge about how health literacy is dispersed through a group of individuals or a community is considered – distributed health literacy – as coined by Edwards et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that social support networks are not static. Rather they are dynamic, variable and subject to stigma (Ciambrone, 2002;Green, Atuyambe, Ssali, Ryan, & Wagner, 2011;Kebede, 2012) and their capacity for support can be strengthened with the inclusion of key individuals, groups, services and online supports, in response to changing needs (Cheong, Armour, & Bosnic-Anticevich, 2015;Smith & Christakis, 2008).…”
Section: The Role Of Social Network In Hiv Self-managementmentioning
confidence: 99%
“…The relationships that bind and integrate people within social networks are also the pathways that determine individuals' exposure to, ideas, practices, opportunities risks, norms and, importantly, social support (Berkman et al, 2000;Smith & Christakis, 2008;Valente, 2012). Moreover, people adapt to new circumstances and change behaviours through social comparison, observing what others do, modelling on those in similar situations and taking advice from those whose opinion they trust and respect (Cheong et al, 2015;Vassilev et al, 2014).…”
Section: Social Network and Healthmentioning
confidence: 99%
See 1 more Smart Citation